Political polarization: a curse of knowledge? - Beattie, Peter; Beattie, Marguerite (Frontiers in Psychology, 2023)
Purpose: Could the curse of knowledge influence how antagonized we are towards political outgroups? Do we assume others know what we know but still disagree with us? This research investigates how the curse of knowledge may affect us politically, i.e., be a cause of political polarization. Background: Research on the curse of knowledge has shown that even when people are incentivized to act as if others do not know what they know, they are still influenced by the knowledge they have. Methods: This study consists of five studies consisting of both experimental and non-experimental and within-and between-subjects survey designs. Each study collected samples of 152-1048 using Prolific. Results: Partisans on both sides overestimate the extent to which stories from their news sources were familiar to contrapartisans. Introducing novel, unknown facts to support their political opinion made participants rate political outgroup members more negatively. In an experimental design, there was no difference in judging an opponent who did not know the same issue-relevant facts and someone who did know the same facts. However, when asked to compare those who know to those who do not, participants judged those who do not know more favorably, and their ratings of all issue-opponents were closer to those issue-opponents who shared the same knowledge. In a debiasing experiment, POLITICAL POLARIZATION: A CURSE OF KNOWLEDGE? 2 those who received an epistemological treatment judged someone who disagreed more favorably.This research provides evidence that the curse of knowledge may be a contributing cause of affective political polarization.